Hazardous materials and hazardous waste management - Woodside, Gayle (John Wiley & sons, Inc, 1999)
The first book to provide coherent treatment of both hazardous materials and waste management in one volume, the Second Edition of Hazardous Materials and Hazardous Waste Management secures this reference's well-earned position in the professional's library as a source of solid, timely technical information.